The judicialization of politics in Asia - Dressel, Bjorn (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2012)
'Over the last two decades courts have become major players in the political landscape in Asia. This book assesses what is driving this apparent trend toward judicialization in the region. It looks at the variations within the judicialization trend, and how these variations affect political practice and policy outcomes.'--Publisher's description.
The judicialization of politics in Asia : towards a framework of analysis / Bj$1'Xr(Bn Dressel -- The judicialization of Japanese politics? / Tom Ginsburg and Tokujin Matsudaira -- Causes and conditions for sustainable judicialization of politics in Korea / Jongcheol Kim and Jonghyun Park -- The judiciary, policy, and politics in India / Shylashri Shankar -- Thailand : judicialization of politics or politicization of the judiciary? / Bj$1'Xr(Bn Dressel -- Indonesia's Constitutional Court : conservative activist or strategic operator? / Simon Butt -- From judicialization to politicization of the judiciary : the Philippine case / Alejandro N. Ciencia -- The judicialization of politics in Pakistan / Charles Kennedy -- China's Supreme People's Court within the'political-legal system' / Shumei Hou and Ron Keith -- Cambodia's judiciary : heading for political judicialization? / Kheang Un and Sokbunthoeun So -- Malaysia : limited and intermittent judicialization of politics / Chandra Kanagasabai -- Leadership, law, and legitimacy : reflections on the changing nature of judicial politics in Asia / Haig Patapan.s
Includes bibliographical references and index.
Keywords: Courts -- Political aspects -- Asia; Political questions and judicial power -- Asia; Law -- Political aspects -- Asia; Justice, Administration of -- Asia; Asia -- Politics and government -- 21st century